Evaluating experiences of healthcare providers and administrators for LGBTQ+ inclusive care and affirmative practices - Saunders, Tiasia (Kansas State University, 2022)
Background: Affirmative care has been recognized as a best-practice form of service for the LGBTQ+ population. However, little is known about what health care providers and administrators are doing to transform towards affirmative and inclusive care practices. The purpose of this study was to: (1) measure the experiences of providers and administrators on their affirming and inclusive practices or those who are in the process and (2) provide recommendations for sustainable affirming and inclusive care practices. This study sought to develop a new instrument to measure the experiences of health care providers and administrators, including awareness, barriers, knowledge, and resources of the LGBTQ+ community. Methods: A mixed-methods approach was used to obtain qualitative and quantitative data. An online survey was sent via email and electronic flyer to health care providers and administrators to evaluate experiences of becoming more affirming and inclusive by transforming their practices. Essential components from the literature that enable the incorporation of LGBTQ+ inclusive care practices were assessed. Results: Health care providers and administrators (N = 159) from across 11 different states answered the online survey. The survey instrument achieved acceptable internal validity (Cronbach’s alpha = 0.7). Organizational change in health care is challenging but achievable. With support, incremental and sustainable changes are possible and would benefit the patient population in receiving optimal care. Conclusions: Essential components from the literature were detailed. Notably, among the health care providers and administrators responding, there were limited barriers to transforming their environment. Future implications for research show that openness, vulnerability, curiosity, and other personality traits should be considered along with education, physical environment, and training. This research provides a structure that hospitals and other health care and public health organizations can use to better align their facilities with inclusive and affirmative health care practices.
Keywords: LGBTQ+; Affirmative care; Inclusive practices; Affirmative and inclusive care practices; Health care environment